Review on Suchikabarana Rasa - Sreelakshmi, K; Kadibagil, Vinay R; Sangameshwara, VK; Anjali, D (Journal of Drug Delivery and Therapeutics, 2019)
Effect of Chikista (treatment) is depend upon many factors like Aushadha (formulations), Aushadha Marga (route of drug administration). Selection of Aushadha Marga (route of drug administration) depend many factors like Aushadha Kalpana (dosage forms), Roga Avastha (condition of disease). Aushadhi (formulation) which is used in Athyayika Avastha (emergency conditions) like Murcha (unconsciousness), Sarpa Dhamsa (snake bite) should be more potent. In Ayurvedic classics different Aushadha Marga (route of drug administration) are mentioned. Suchikabarana Rasa is one of the formulations mentioned for subcutaneous route in Sarpa Dhamsa (snake bite). It is prepared by Sthavara Visha (plant or mineral poison) and Jangama Visha (animal poison) which is more effective in small dose. Visha Dravya (poison drugs) act quick and effective in small dose because of their Guna (property).